Oxo and Oxyfluoro Complexes of Iodine (V) and (VII) - Krasznai, Julius John (My University, 1975)
The behaviour of potassium iodate, iodic acid and various other iodine V compounds as solutes in fluorosulfuric acid has been studied using cryoscopy, conductivity, Raman and nmr spectroscopy. Evidence has been obtained for the species IOF₂SO₃F as the major product of the reactions, and this species has been shown by Raman spectroscopy to be fluorosulfate bridged. The IO₂⁺ and IOF₂⁺ cations have been prepared from the corresponding oxyfluorides and a strong fluoride ion acceptor and characterized for the first time.
The structure of IO₂F₃ has been the subject of several publications and although they all agree that the molecule is polymeric, no definite conclusion on the polymer size had been reached. It has been shown in this work, that IO₂F₃ is a cis oxygen bridged trimer in the solid, liquid and solution phases. The chemistry of IO₂F₃ with strong Lewis acids was studied and it was found to be a fluoride ion acceptor forming polymeric complexes of the type (IO₂F₄ MF₄)n. The previously unknown salt KIO₂F₄ was prepared and characterized and it was found to exist as the trans isomer in the solid and in acetonitrile solution but as a mixture of cis and trans in solvents where fluoride ion transfer can occur. IOF₅ has previously been shown not to be a fluoride ion donor but the ¹⁹F nmr and Raman spectrum of solutions containing IOF₅ and SbF₅ indicated an interaction between IOF₅ and the Lewis acid through the oxygen. At low temperature in SO₂F₂ as a solvent, 1:1 and 1:2 complexes were observed. An attempt to prepare periodyl fluoride IO₃F, the last of the series of iodine (VII) oxyfluorides proved unsuccessful.
Keywords: Chemistry; Chemistry